Pengaruh Cadangan Kerugian Penurunan Nilai dan Net Interest Margin terhadap Profitabilitas pada Unit Usaha Syariah - Nana Diana; Safitriana Limbong (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this research is to analyze the effect on Profitability described by Return on Assets that can be influenced by Allowance for Impairment Losses (CKPN) and (NIM). The research method uses descriptive and verification methods. In this study, the Allowance for Impairment Loss (CKPN) variable is used as the X1 variable, the Net Intrest Margin (NIM) as the X2 variable and the Return On Asset (ROA) variable as the Y variable. The population in this study is Sharia Business Units registered with OJK with a quantity of 20 Sharia Business Units. Purposive sampling technique was used as a determinant of sampling so that the sample studied was 6 sharia business units, the data used came from the annual financial ratio reports for each sharia business unit contained in the Financial Services Authority (OJK). obtained in 2016 – 2021. The results of the partial study of CKPN cannot affect ROA but the NIM variable shows it can affect ROA, and simultaneously both cannot affect ROA of Sharia Business Units registered with OJK 2016-2021. Keywords: CKPN, NIM, ROA